Epistemology of al-Hukm al-Taklifi in Islamic Family Law: Integrating Haqq and Iltizam as the Normative Foundation of the Kompilasi Hukum Islam in Indonesia - Agustin Hanapi; Muhammad Husnul (TAQNIN: Jurnal Syariah dan Hukum, 2025)
This study explores the epistemology of al-hukm al-taklifi in explaining the integration of haqq (rights) and iltizam (obligations) as the normative foundation of the Kompilasi Hukum Islam (KHI) in Indonesia. It aims to reconstruct the moral coherence of Islamic family law by grounding it in the epistemic structure of taklif. Using a qualitative, normative-philosophical approach, the study analyzes classical texts of usūl al-fiqh-including works by al-Ghazali, al-Āmidi, and al-Shaṭibi-alongside modern legal thought on Islamic normativity and pluralism.The findings reveal that al-hukm al-taklifi functions as an epistemic bridge linking divine revelation, rational cognition, and moral purpose. The codification of the KHI, however, has fragmented this unity by emphasizing legal form over ethical substance. Reintegrating haqq and iltizam within taklif restores law's moral dimension and theological legitimacy.The study concludes that reform in Islamic family law must begin with epistemological reconstruction. The implications suggest that taklif provides a universal framework for harmonizing revelation and reason, transforming Islamic law into a living moral discourse grounded in justice, compassion, and wisdom.